Therapeutic workshop in Nursing: Extension experience in the care and development of people with disabilities (Research, Society and Development, 2025)
The care of people with disabilities requires a comprehensive approach focused not only on clinical treatment but also on promoting autonomy, social inclusion, and quality of life. In this context, nursing plays a fundamental role by integrating educational, therapeutic, and humanized actions. This study aimed to report the extension experience developed by nursing students at the Associação de Pais e Amigos dos Excepcionais (APAE) in Redenção – PA, through the project “Therapeutic Workshops as a Tool for the Development of People with Disabilities: The Role of Nursing.” The workshops were designed based on playful, artistic, and educational practices, including reading, storytelling, and adapted manual activities. The results showed significant progress in the cognitive, motor, and emotional development of the participants, as well as increased socialization and strengthened self-esteem. It was also observed that participation in the workshops promoted autonomy and self-care, reaffirming the potential of therapeutic practices in the context of inclusive health. For the students, the experience enabled the consolidation of technical, ethical, and relational skills, fostering a more sensitive education committed to the principles of equity and humanization. It is concluded that therapeutic workshops represent an effective strategy for care and inclusion, reinforcing the role of nursing in promoting the integral development of people with disabilities.